Impacto de las políticas públicas sobre el servicio de agua potable en los habitantes del cantón el Carmen periodo 2019-2022 - Muñoz Mera, Jervi Jair (2023)
This research work was carried out with the objective of analyzing the impact of public policies implemented by the Decentralized Autonomous Government in El Carmen canton on the drinking water service for the benefit of the population, period 2019-2022. Several methods such as inductive, deductive and analytical-synthetic were used, which allowed the construction of true data of the demonstrated facts, also, a structured interview with the director of drinking water and sewerage of the institution was used as an information gathering technique, where he stated that they are working on various public policies to provide a quality service. On the other hand, surveys were applied to the different urban parishes such as: El Carmen and the 4 de Diciembre parish; and the rural parishes Wilfrido Loor Moreira (Maicito), San Pedro de Suma and El Paraíso - La 14, where detailed information was obtained on the problems that exist in the drinking water service such as water quality, pressure, duration and service distribution to all sectors. These results were tabulated through the Excel tool, which made the analysis easier. Finally, an improvement plan was designed with strategies that were used to mitigate the existing shortcomings in the public policies of the drinking water service, which was socialized with the people involved in the investigation.